DETECTING THE APICAL CONSTRICTION IN CURVED MANDIBULAR MOLAR ROOTS— PREFLARED VERSUS NONFLARED CANALS - Khan, Irfan ullah; Sobhi, Muhammad Baksh (Journal of Ayub Medical College Abbottabad, 2003)
Bckground: Achieving and maintaining correct working length is critical to success in endodontic therapy. This involves placing the file in to the canal to feel the apical constriction, preparing the canal upto that extent and then filling the entire canal upto the apical constriction with gutta percha points. Detection of the apical constriction is affected if the coronal part of the canal is narrow or obstructed due to dentine deposition. This usually happens in curved canals and gives the operator a false feeling of the apical constriction. The aim of this study was to compare the effect on tactile detection of apical constriction in mandibular molars with curved roots, between the preflared and non-flared root canals. Methods: This study was carried out at Armed Forces Institute of Dentistry, Rawalpindi, Pakistan, from February to April 2002. Seventy patients coming for the endodontic treatment of their mandibular first molars were selected. The study included only mandibular molars with curved mesial canals. The total no of patients were divided equally into the preflared and non-flared groups. In both groups a No. 15 K file was used to detect or feel the apical constriction but in the preflared group the coronal portion of the canal was flared/prepared using Hedstrom files (No. 25-55) and Gates Glidden Drills No. 02 to No. 05 before inserting the No. 15 file. The tooth was radiographed at this moment and the distance between the tip of the file and the radiographic apex was measured. The location of the tip was classified as: a) Within 1 mm of the radiographic apex, b) Under extended, more than 1 mm of radiographic apex, and c) Over extended, beyond the radiographic apex. Results: In the non-flared group 31.4% belonged to group ’˜a’, 40% to group ’˜b’, and 28.57% to group ’˜c’. In the flared group 80% belonged to group ’˜a’, 5.7 % to group ’˜b’, and 14.28% to group ’˜c’. Conclusions: Results of this study suggest that preflaring greatly improves the tactile sense to feel the apical constriction in curved canals. Key words: Preflaring; Apical constriction; Curved canals; Mandibular molars; and Working length.